Reprezentatywność w badaniach marketingowych - potrzeba nowego spojrzenia - Oczachowski, Dariusz; Oczachowska, Alina (Representativeness in Marketing Research - the Need for a New View, 2008)
Theoretical marketing and marketing research have already a hundred-year history. Because they are descended from economy, they have always been are dependent on it. One of the indications of this dependence is distinct dominance of statistical and representative orientation in sampling, particularly in questionnaire surveys. Such attitude, being the consequence of the orthodox scientism, does not prove to be an adequate approach nowadays when changes in the market are so fast. Under such conditions the advantage of random (probability) methods seems only apparent, creating and sustaining the illusion of mathematical precision. An heterodox attitude is needed accepting methodological pluralism in the matter of representativeness, aware of the limitation of probability sampling methods and of the equivalence of non-probability sampling where it is impossible to prove the superiority of the probability sampling methods techniques. It mainly concems the most popular ąuestionnaire surveys with numerous samples, where still valid seems the true of absolute superiority of representative methods as the only guarantor of representatives.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 75-82